2005
DOI: 10.1124/jpet.105.087064
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Effects of the Incretin Enhancer Vildagliptin in Insulin-Resistant Rats

Abstract: The enzyme dipeptidyl peptidase-IV (DPP-4) inactivates the incretin hormone glucagon-like peptide-1 (GLP-1). Because GLP-1 has therapeutic effects in patients with type 2 diabetes, but its potential is limited by a short half-life, DPP-4 inhibition is a promising approach to diabetes treatment. This study examined acute (single dose) and chronic (once-a-day dosing for 21 days) effects of the DPP-4 inhibitor vildagliptin (0.03-10 mg/kg) on plasma DPP-4 activity, intact GLP-1, glucose, and insulin after an oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 32 publications
9
71
1
1
Order By: Relevance
“…6). This effect on insulin impairment has also been reported in GK and neonatal streptozotocin (nSTZ)-induced rats (in the case of SU agents) [12,13] as well as ZDF and ZF rats (in the case of DPP IV inhibitors) [2,25]. The results of our in vivo study on the effects agreed with the finding in isolated islets of SDT rats that insulin secretion is enhanced by tGLP-1 or tolbutamide stimulation (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…6). This effect on insulin impairment has also been reported in GK and neonatal streptozotocin (nSTZ)-induced rats (in the case of SU agents) [12,13] as well as ZDF and ZF rats (in the case of DPP IV inhibitors) [2,25]. The results of our in vivo study on the effects agreed with the finding in isolated islets of SDT rats that insulin secretion is enhanced by tGLP-1 or tolbutamide stimulation (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Previously we have shown that vildagliptin (also called LAF-237) improves glucose tolerance in high-fat fed glucose intolerant mice (25). Vildagliptin also has been shown to augment the insulin response to oral glucose and glucose tolerance in obese Zucker rats (20) and to improve glucose tolerance in ob/ob mice (26) and Zucker diabetic fatty rats (27). The antidiabetic action of vildagliptin relies on increased concentrations of active (intact) GLP-1, since DPP-4 inhibition prevents the inactivation of the incretin hormone (1-3).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the 12th week, rats in each group were divided into three subgroups (nZ10/subgroup) to receive vehicle (normal saline solution; 2 ml/kg per day), vildagliptin (Galvus, Novartis; 3 mg/kg per day), or sitagliptin (Januvia, MSD, Bangkok, Thailand; 30 mg/kg per day) (Chen et al 2011a) via gavage feeding for 21 days. It has been shown that 3 mg/kg per day of vildagliptin and 30 mg/kg per day of sitagliptin reduces peripheral insulin resistance in insulin-resistant and diabetic rat models (Burkey et al 2005).…”
Section: Animal Modelsmentioning
confidence: 99%
“…Recently developed oral anti-diabetic drugs, DDP-4 inhibitors including sitagliptin and vildagliptin, have been used to treat T2DM patients. Previous studies have shown that DDP-4 inhibitors decrease insulin resistance without causing severe hypoglycemia (Burkey et al 2005, Richter et al 2008, via prolonged levels of endogenous active GLP-1(7-36) amide (Rosenstock & Zinman 2007, Richter et al 2008. GLP-1 is an incretin hormone secreted from intestinal L-cells following nutrient digestion, which causes decreased glucagon secretion and increased insulin sensitivity (Baggio & Drucker 2007).…”
Section: Introductionmentioning
confidence: 99%